2009
DOI: 10.3342/ceo.2009.2.2.97
|View full text |Cite
|
Sign up to set email alerts
|

CSF Otorrhea Resulting from Osteoradionecrosis of the Temporal Bone in a Patient with Recurrent Meningioma

Abstract: Osteoradionecrosis of the temporal bone is a very rare but potentially lethal complication of radiotherapy for head and neck or skull base tumors. Only two cases of osteoradionecrosis of the temporal bone complicating cerebrospinal fluid (CSF) otorrhea have been reported in the literature. This report describes a case of CSF otorrhea and osteoradionecrosis of the temporal bone in a patient with meningioma who was treated with tympanomastoid surgery and autologous fat obliteration in the mastoid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The mandible is one of the most frequently affected bones 2,6,11,[17][18][19] . ORN has been reported as the major complication of irradiation in head and neck cancer 2,[5][6][7]11,13,[20][21][22] . However, many etiologic factors of ORN have been reported in the Conservative treatment of osteoradionecrosis literature.…”
Section: Case Reportmentioning
confidence: 99%
“…The mandible is one of the most frequently affected bones 2,6,11,[17][18][19] . ORN has been reported as the major complication of irradiation in head and neck cancer 2,[5][6][7]11,13,[20][21][22] . However, many etiologic factors of ORN have been reported in the Conservative treatment of osteoradionecrosis literature.…”
Section: Case Reportmentioning
confidence: 99%
“…It is important to recognize this entity because the diagnosis may preclude potentially harmful diagnostic intervention and allow more appropriate therapy [38]. The temporal bone has been affected by ORN after irradiation of nasopharyngeal carcinomas [39,40].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Cholesteatoma may occur as a result of chronic tympanic membrane perforation or fistula formation directly into the mastoid cavity. Labyrinthitis, 9,14 cerebrospinal fluid leak, 12,29,30 cerebellar abscess, 21 temporal lobe necrosis, 15 sigmoid sinus thrombosis, 4,14 and internal carotid artery aneurysm 4,31,32 have also been reported. Finally, in their series of 33 patients, Hao et al reported that tumor recurrence or radiation-associated malignancy was misdiagnosed as ORN in 21% of cases.…”
Section: Diagnosis and Classificationmentioning
confidence: 99%
“…Nearly 400 cases are described in the literature, predominantly through the publication of institutional case reports and retrospective case series. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Despite increasing awareness, ORNTB remains a debilitating and potentially lethal condition that continues to challenge patients and treating physicians.…”
mentioning
confidence: 99%